Patient Involvement in Teaching and Assessing Entrustable Professional Activities of Competence by Design - Adam, Holly Lynne (Université d'Ottawa | University of Ottawa, 2025)
Background: Active patient involvement (i.e., patient involvement in teaching, assessment, or in roles at institutional levels) in medical education has many benefits for learners. It brings realism to education, helps learners retain information, helps learners reflect on their interactions with patients, and improves learners’ interpersonal and communication skills. Furthermore, the Royal College of Physicians and Surgeons of Canada (i.e., RCPSC; the regulating body for postgraduate medical education) endorses patient involvement in assessing residents. However, the extent of patient involvement in postgraduate medical education (PGME) in Canada is unknown. This study explores this phenomenon, namely, how (or if) patients are indicated and involved in entrustable professional activities (EPAs; sets of skills and competencies that are entrusted to a professional and compose medical education curricula) of Competence by Design (CBD), a Canadian hybrid approach of competency-based medical education. Specifically, it explores (a) how patients are indicated in a sample of RCPSC EPA documents; (b) how (or if) those involved with EPAs envisioned patients in the teaching and assessment of EPAs, during EPA creation; and (c) how (or if) patients are (or could/should be) involved in the teaching and assessment of EPAs. This study adds to the limited knowledge available on patient involvement in PGME in Canada. It illuminates medical educators’ perceptions of patient involvement in medical education and barriers to patient involvement that must be overcome for it to become reality in the teaching and assessment of EPAs and CBD overall. Methods: I conducted this study in two parts, using qualitative methods. Part 1 involved analyzing a sample of RCPSC EPA documents for how patients are indicated in them. Part 2 involved semi-structured interviews with those involved with EPAs to explore (a) how (or if) patients were discussed in the teaching and assessment of EPAs, during creation; (b) how (or if) patients could (or should) be involved in the teaching and assessment of EPAs; and (c) barriers to patient involvement in the teaching and assessment of EPAs. Findings: The findings suggest that patients are indicated in EPA documents passively compared to physicians, which minimizes opportunities for active patient involvement in the teaching and assessment of EPAs. Interviews with those involved with EPAs suggested that patients were discussed during EPA creation in terms of how patients could assess EPAs, not in terms of how patients could teach them. Those involved with EPAs believed that patients should formatively assess non-technical skills of EPAs (i.e., the cognitive, social, and personal skills that work together to contribute to quality health care and effective physician-patient interactions; Flin et al., 2008). They also believed that patients should contribute to the formative assessment of EPAs and that patients could teach non-technical aspects of EPAs through storytelling. However, participants recognized that patient involvement in the teaching and assessment of EPAs is limited due to barriers, including finding the ‘right’ patient, lack of time, risk of breaking patient anonymity, and technology. Findings of this study provide recommendations on how to improve patient involvement in the teaching and assessment of EPAs.
Keywords: patient involvement; competence by design; medical education; entrustable professional activities; EPA teaching; EPA assessment